Body composition changes differ by gender in stomach, colorectal, and biliary cancer patients with cachexia: Results from a pilot study. (3rd July 2018) - Yoon, Saunjoo L.; Grundmann, Oliver; Williams, Joseph J.; Gordan, Lucio; George, Thomas J.
Abstract: Few studies have examined the possibility that cachexia may affect men and women differently. This pilot study assessed gender differences in body composition in stomach, colorectal, and biliary cancer patients with cachexia. A sample of 38 participants (Female: Male = 17:21, mean age 57.4 years) were included if they were undergoing chemotherapy and experienced weight loss of 5% or more over a 6‐month period. Bioelectrical impedance analysis (BIA) was applied to measure body composition. Phase angle (PA) and levels of extra‐/intracellular water (ECW; ICW) were determined. Data were analyzed first by gender and then compared to age‐ and gender‐matched healthy controls from the NHANES‐III dataset. PA was lower ( P < .01) in both genders compared with healthy controls, and PA was lower in female patients compared with male patients ( P = .03). Male cancer patients with lower PA also had lower ICW levels compared with healthy controls ( r = .98, P < .01). For female patients, PA and ICW were negatively correlated ( r = .897, P < .01). A lower ECW/ICW ratio was highly correlated ( r = .969 for men, r = .639 for women) with increased PA in cancer patients. ICW changes are gender‐specific in patients with GI cancer. ECW/ICW ratios and PA may be suitable surrogate markers for gender‐specific changes in cell composition and health status. Abstract : Body composition may be gender dependent in patients with gastrointestinal cancer and require differential diagnosis and treatment approaches. Determination of sarcopenia and cachexia should utilize changes in intracellular/extracellular water ratio in addition to phase angle dependent of gender.